Development of android-based immune system learning media SMA Negeri 6 Sidrap - Nur Atifah Tamrin Atifah; Nurmayanti Nurmayanti; Agussalim Agussalim (Institute of Computer Science (IOCS), 2023)
This android application-based learning media is an interactive teaching material that can facilitate students in the learning process. the purpose of the research is to produce valid and practical android-based learning media in Biology subjects to facilitate the learning process. The research method used is Research and Development (R&D) by applying the 4D model with stages: 1) Define, 2) Design, 3) Develop, 4) Disseminate. Data were obtained through observation, interview, and questionnaire techniques. Data processing was carried out with quantitative descriptive techniques using formulas and validation criteria and practical criteria. The results showed that based on the validation test by material experts and media experts, it was declared very valid with a percentage value of 83.2%. While the results of the assessment of the teacher's response were declared very practical with a percentage value of 97.14% and the results of responses from students were declared very practical with a percentage value of 84.97%. Based on the data obtained, it can be concluded that the development of learning media based on android applications is declared feasible for use in the Biology learning process